ESTIMACIÓN DEL TOTAL POBLACIONAL USANDO EL ESTIMADOR DE DIFERENCIA - Gutiérrez, Hugo Andrés; Breidt, F. Jay (Revista Colombiana de Estadística, 2009)
This paper presents a new regression estimator for the total of a population created by means of the minimization of a measure of dispersion and the use of the Wilcoxon scores. The use of a particular nonparametric model is considered in order to obtain a model-assisted estimator by means of the generalized difference estimator. First, an estimator of the vector of the regression coefficients for the finite population is presented and then, using the generalized difference principles, an estimator for the total a population is proposed. The study of the accuracy and efficiency measures, such as design bias and mean square error of the estimators, is carried out through simulation experiments.